Design and Development of a Thesis Borrowing and Returning System - ดาวเรือง กษิดิศ; มีนคร สมศักดิ์; ปั้นคำ วิทยา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to design and develop a thesis borrowing and returning system. The case study is based on the Industrial Management Technology program, Faculty of Engineering, Thonburi University, where the existing system relies primarily on manual data entry. This approach has led to frequent errors, inefficiencies, and delays in operation. To address these problems, a new system was developed to enhance operational efficiency, reduce data entry errors, and facilitate more convenient information retrieval. The target group includes students and related personnel. Data collection and root cause analysis were conducted using fishbone diagrams and the Why-Why Analysis technique. The results revealed that the original system suffered from low efficiency and delays due to manual data handling. Consequently, a new system was developed using Visual Basic as the programming language and Microsoft Access as the database. The improved system reduced the borrowing time from 120 seconds to 50 seconds, and the returning time from 100 seconds to 45 seconds, while also minimizing data entry errors. Preliminary testing indicates that the new system significantly improves efficiency, accuracy, and user convenience compared to the previous system.